M271 A Survey Of Trainee Experiences In Interstitial Lung Disease. (10th November 2014) - Sharp, C; Gibbons, M
Abstract : Interstitial lung disease (ILD) is a major area of respiratory medicine It is important that trainees gain competence and confidence in this area. Methods: A survey of BTS trainee members was conducted in November 2013 to examine training provision in ILD, including trainee's opportunities, experience and confidence in aspects of ILD. Results: There were 104 respondents out of a possible 574. 33% of respondents were not expecting any subspecialty clinics in ILD in the course of their training. 42% of trainees expect to spend 3 months or less attending specialist clinics. Trainee attendance at MDTs is far from guaranteed, with 45% expecting to attend less than half during their period in these hospitals. The majority of trainees are trained in performing BAL for cell differential analysis (73%) and transbronchial biopsies (84%), however only 48% are confident performing transbronchial biopsies. Confidence interpreting investigation results increases with the frequency these are performed. The self rated knowledge in a range of subject areas was also assessed and demonstrated that most areas were moderately well understood, however knowledge of the less frequently encountered IIPs was rated lower. 54% of trainees felt their ILD training was inadequate for SCE preparation. 94% would value a BTS Short Course on ILD to improve their knowledge and confidence. Discussion: This survey highlights areas where there are clear opportunities to enhance the training of registrars in ILDs. It is worth noting that some of the data is in conflict with previous BTS surveys in this area and there is the possibility of self-selection bias in the response population. Whilst most trainees are trained in performing relevant procedures, their confidence interpreting the results of common investigations in ILD is low. To give evidence of training and competence in this area, deaneries may wish to consider requesting logbook evidence of procedures related to ILD, in addition to evidence of ILD MDT attendance. There is undoubtedly a need for a BTS short course on ILD for trainees.